Limitations of the Physical Activities in Asthmatic Children and Teenagers - Sánchez, Hernán; Canseco González, Carlos; González Díaz, Sandra Nora; Arias Cruz, Alfredo
The asthma can be direct or indirect cause of physical limitations in asthmatic patients affecting their quality of life.